Fatores associados à qualidade de vida de idosos de uma Universidade Aberta para Maturidade - Marinho, Jaciara Ribeiro Terra (2019)
A good aging can be understood as a lower probability of disease, high functional capacity, physical and mental, and active social engagement with society. The reach of these factors requires Health Promotion (PS) and aging with Quality of Life (QoL), emphasizing the preventive and assistance aspects of greater relevance among the elderly population. The objective of the study was to evaluate QoL and to identify factors associated with it, to describe the socio-demographic and socioeconomic profile and to evaluate the anthropometric data of the elderly of the Open University for Maturity (UNABEM). This is a quantitative observational research, with descriptive and analytical characteristics and cross-sectional characterization carried out in a municipality in the interior of the state of Minas Gerais. The sample consisted of 88 elderly people. Data were collected between April and June 2017. The instruments were: semi-structured questionnaire to trace the socio-demographic profile of the elderly, the Brazilian Economic Classification Criterion (CCEB) for socioeconomic data, the Mini Nutritional Assessment (MAN) and the Body Mass Index (BMI) to evaluate the anthropometric data and the WHOQOL - BREF and WHOQOL - OLD to evaluate the QoL. Data were analyzed in the form of arithmetic means, standard deviations for the numerical variables and relative and absolute frequencies for the categorical variables. In the results, women, married / kneeling, with a mean age of 69.7 years and less than one year of participation in UNABEM (37.5%) predominated. 75% of the elderly were retired, with an average income between one and two minimum wages. According to the BMI, 65.9% of the elderly were overweight, 29.5% were eutrophic and 4.5% were underweight, which differs from MAN's results, in which 81.8% were adequately weighed and 18, 2% were malnourished. Systemic arterial hypertension (SAH) was the most prevalent disease among the elderly (22.7%), followed by hypertension with other associated diseases (15.9%) and hypertension and diabetes (12.5%). In WHOQOL-BREF, there was a good perception of QOL, and Health satisfaction was regular. The elderly showed an average general QOL of 71.73 and it was verified that the best perception of QoL was attributed to the psychological domain (69,79), followed by the physical domain (67,17) and social relations (64,87) and the lowest domain was the environment (63,81). In WHOQOL-OLD, the overall score was 63.21, and the domains with the highest values were functioning of the sensorium (74.9) and death and dying (70.6), past, present and future activities (60.7) and those with lower values were intimacy (54.83), autonomy (58.31) and social participation (59.9). These results can contribute positively to the elaboration and expansion of PS and QV programs and promote greater interaction and socialization within this population, providing them with a conscious, active, healthy and QL aging.